TEACHERS’ PROFESSIONAL COMMITMENT AS AN INDICATOR OF PSYCHOLOGICAL READINESS TO THE PROFESSIONAL STANDARDS IMPLEMENTATION - S. A. Minyurova; A. I. Kalashnikov (Образование и наука)
Introduction. Nowadays, the problems of motivation of modern teachers and their valuable relation to the profession are actively being discussed in the scientific and pedagogical community. The changes in the relations between an employer and a teacher have been caused by the introduction of professional standards of the teacher and the extending practice of the conclusion of the socalled "effective contracts" between educational institutions and teachers. The aim of the present publication is to consider a phenomenon of professional commitment of teachers as a criterion of their psychological readiness for acceptance of new realities caused by the changed qualification competences having been imposed by the professional standard. Methodology and research methods. Comparative analysis and synthesis of the approaches to studying of a phenomenon of professional commitment existing in foreign psychology have been used. The empirical research of commitment of the Russian teachers to the profession was conducted on the basis of the authors’ method “The Questionnaire of Professional Commitment”. Statistical processing of the data obtained during the survey was carried out on the basis of the Statistica 7.0 program. The method of the factor analysis was applied. Results and scientific novelty. Yet, most studies in the field of the problematics of professional commitment have predominantly been carried out by foreign scholars. The attempt to describe the research experience on studying of professional commitment of the Russian teachers has been made for the first time ever. The proposed models of professional commitment are compared. It is proved that the structure of each model depends on professional and cultural diversity of a target group of a specific study. The specific features of psychological content of professional commitment of the Russian teachers are designated. Based on the systematized results of survey, the key structural components of teachers’ commitment can be listed as follows: “professional affectivity” (identification and emotional attachment to the chosen specialty, satisfaction with the calling, feeling of professional pride, acceptance of the goals and values), “professional stability” (feeling of resignation challenges, feeling of a professional duty), and “professional activity” (feeling of full-time commitment and complete dedication, spending free time and energy for the sake of professional self-realization). It has been concluded that teacher’s awareness to adopt strict professional obligations is followed by the feeling of enormous emotional expenditure of the chosen profession, being one of the reasons for the increased uneasiness and low readiness of teachers to introduction of the professional standard. Practical significance. The article provides an interpretation of the available information for a better understanding of the teacher professional commitment specifics. The materials of the present article can be useful when developing the programmes for educators’ commitment to the profession.